Behavior Factors Of Ppe Use (Masks) Against Disorders Of Working Respiratory System Cigarette Factory - Wiwit Pujaka Susanti; Aprin (Universitas STRADA Indonesia, 2019)
Cigarette factory is a work environment that has dust exposure from tobacco processing. Piles of tobacco containing nicotine and tar that have a strong scent also cause a feeling of tightness in the chest. Personal protective equipment (PPE) in the form of a mask plays an important role in protecting the respiratory system from the negative effects caused by cigarette factories where the mask functions to protect the respiratory system from dust, chemical, steam, smoke, gas/fume and mist (aerosol). The method in this research is literature riview and data search based on 3 database that is google scholar, pubmed, research gate. The articles used are national and international articles by using several key words such as respiratory system disorders, cigarette factory workers, wearing PPE mask, cigarette factory worker behavior and the tobacco industry with journal publication in 2015-2020. Based on the results of a riview of seven articles that focus on cigarette factories, there is a conclusion that dust and odor are the main problems complained by cigarette factories workers and respiratory system disorders are a result of workers disobedient in the use of PPE mask caused by workers bad behavior. Workers behavior is influenced by length of work regulations, support of co-workers and support of leaders. It cannot be denied that cigarette factories have a great risk to the health problems of their workers, one if which is a respiratory system disorder caused by workers behavior that is not compliant in using PPE mask at work.